Oil quality of exotic safflower (Carthamus tinctorius L.) cultivars in India: OIL QUALITY OF EXOTIC SAFFLOWER CULTIVARS IN INDIA - P KADIRVEL; PRADUMAN YADAV; N MUKTA (Journal of Oilseeds Research, 2017)
Improvement of oil content and quality are important goals in safflower breeding. In this study, a set of 10 high oil exotic safflower cultivars were evaluated at Hyderabad (India) for oil content and fatty acid composition in order to assess their suitability for Indian safflower breeding programmes. Oil content in the exotic varieties ranged from 35.3 per cent (Finch) to 41.4 per cent (Centennial). Overall, the exotic varieties showed about 5 to 10 per cent increase in oil content over the most popular Indian high seed yielding varieties A-1 and Bhima. Furthermore, six varieties showed high oleic acid content ranging from 70.0 per cent to 80.2 per cent. The exotic varietal sources reported in this study would be helpful to expedite breeding high oil-high oleic safflower cultivars in India.